Conflict Management: Building the Dynamics of Leadership in Islamic Educational Institutions - Almuhajir, Almuhajir (Islamic Educational Management Programme, 2022)
This study aims to explain conflict management in building leadership dynamics in Islamic educational institutions. This research is a literature review with a conflict management approach to educational institutions. Conflict management is an effort that needs to be dontoto prevent, avoid conflicts and reduce risks and resolve conflicts so as not to interfere with organizational performance. Conflict is somethilt to avoid in an Islamic educational institution. If managed properly, conflict will dynamize Isthe lamic educational institutions in a positive directipositivelylamic education institution must have the authority for his leadership potential in managing conflict to guide and control the behavior and actions of his subordinates and be well-coordinated so that dynamics that can produce change and development for the better can be realized effficiently.